PROJECT-ORIENTED PROBLEM BASED LEARNING (POPBL): AN INITIATIVE TO ENHANCE SELF-ESTEEM AMONG ORPHANS - Fatmawati Latada; Husna Hashim (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Self-esteem is embodied by a person when he feels capable of handling life’s basic challenges and being worthy of happiness. Countless studies unfortunately indicated that orphans are often deficient of this quality. This paper explores and discusses the implementation of Project-Oriented Problem Based Learning (POPBL) in an orphanage to boost the participants’ self-esteem. The study involved 32 male orphans aged 9 to 16 years old, coming from diverse backgrounds and originated from various parts of Malaysia. Participants were divided into three groups of 11 and 10 members, and each led by a male supervisor or warden. Each group was required to manage and participate in a program called “Sayyidul Ayyam’. The program took place on specified Fridays, and all three POPBL sessions were completed within two months. Each orphan in each group was entrusted with specific roles such as master of ceremony (MC), reciter of the Quran, reciter of the meaning of the Quran, storytellers, Nasyid presenters and finally Doa reciter. Each group was given two weeks to practice prior to their designated Friday and were given the freedom to choose their own roles, their own nasyid etc. Participants’ self-esteem levels were assessed using The Rosenberg Self-Esteem Scale (RSES) before and after completing their tasks. To ensure RSES items were understood by minor participants, individual interviews were conducted to collect data. The RSES uses a scale of 0–30, where a score less than 15 suggested low self-esteem. The findings indicated that after completing the POPBL program, 62.63% (N=20) of the participants demonstrated improved self-esteem, 21.22% (N=7) reported no change, and 15.15% (N=5) experienced a decrease in their self-esteem level. The findings were shared with the Pahang Orphan Welfare Association (PEKAYA) aiming to facilitate its members to adopt the Problem-Based Project-Based Learning (POPBL) module as a tool to strengthen their residents’ self-esteem.